Intertidal wetland geomorphology influences main channel hydrodynamics in a mature barrier estuary. (5th April 2022) - Kumbier, Kristian; Hughes, Michael G.; Carvalho, Rafael C.; Woodroffe, Colin D.
Abstract: Previous research utilising water level observations and hypsometric data has suggested that intertidal areas exert some control on main channel flow dynamics in estuaries, lagoons and tidal creeks. This has been demonstrated in more detail for saltmarsh and mangrove creeks utilising measurements of tidal velocity. However, understanding of relationships between tidal hydrodynamics and intertidal wetlands is still lacking for mature barrier estuaries. Improved understanding of hydrodynamics in these systems, as well as potential interactions with tidal wetlands, may facilitate their effective management and modelling. This study investigates relationships between main channel hydrodynamics and vegetated intertidal wetlands at Minnamurra River estuary, southeast Australia, using observations of tidal dynamics and wetland inundation regime. Tidal data was collected over five spring-neap cycles utilising tidal gauges and drag-tilt flow meters at six locations in the estuary's main channel, and 14 pressure transducers along three wetland transects. Comparison of stage-velocity plots and hypsometric curves indicates that estuarine flow dynamics were spatially variable and strongly influenced by the geomorphology of intertidal wetlands in the upper estuary, where water surface gradients developing during flood and ebb phases created velocity pulses. Spatiotemporal analysis of tidal asymmetry showed variability along the estuary, as well as between spring and neap conditions. The estuary studied displayed an ebb-dominated deeper main channel (velocity asymmetry) surrounded by wide shallow flood-dominated margins, indicating that caution should be adopted when interpreting an estuary's tidal asymmetry using a single asymmetry characteristic. Overall, results presented here demonstrate a strong connection between estuarine hydrodynamics and vegetated intertidal wetlands, which implies that integrated approaches considering estuarine hydrodynamics and vegetated intertidal wetlands simultaneously are required to manage and model mature barrier estuaries. Highlights: Channel and wetland processes are interlinked in mature barrier estuaries. Upstream main channel velocity accelerates as wetlands flood and drain. Shallow barrier estuaries can display both ebb and flood flow dominance. Tidal asymmetry differs depending on the criteria adopted.